Frontiers of Quantum Chemistry (Springer Singapore, 2018)
The purpose of this book is to convey to the worldwide scientific community the rapid and enthusiastic progress of state-of-the-art quantum chemistry. Quantum chemistry continues to grow with remarkable success particularly due to rapid progress in supercomputers. The usefulness of quantum chemistry is almost limitless. Its application covers not only physical chemistry but also organic and inorganic chemistry, physics, and life sciences. This book deals with all of these topics. Frontiers of Quantum Chemistry is closely related to the symposium of the same name held at Kwansei Gakuin University at Nishinomiya, Japan, in November 2015. The book's contributors, however, include not only invited speakers at the symposium but also many other distinguished scientists from wide areas of quantum chemistry around the world. .